The Existence of Mukim Judicial System in the Context of National Legal System - Hanif Nurcholis; Hanif Hardianto; Salawati Mat Basir; Sri Wahyu Kridasakti; Rina Elsa Rizkiana (Universitas Negeri Semarang, 2026)
The Mukim legal system may be compared to two sides of a coin, with governmental duties and customary functions in the government and customs sections, respectively. Mukim, as a conflict resolution in Acehnese culture and the primary decision-maker in settling disputes, is governed by qanun and has the potential to become a formal institution in the Indonesian national legal system. This is predicated on a juridical-normative basis: the existence of the Mukim, together with all of the political symbols of sovereignty associated with it, is recognised de jure in positive law; but this acceptance appears to be out of sync de facto. The purpose of this study is to examine at how the Mukim evolved from a judicial system to a formal institution within by Legal Effectiveness Theory. This study is a socio-legal case study of Banda Aceh City, Aceh Besar Regency, Bener Meriah Regency, and Central Aceh Regency that employing document review and focus group discussions with Mukim authority holders, as well as content-analysis and legal-synchronicity analysis approaches. The research findings reveal that Mukim, as a customary justice system, is recognised not only at the socio-cultural level of the Acehnese people, but also at the official legal level in Aceh. As a result, the national legal system recognises and confirms Mukim's transition from a customary judiciary to a formal institution.